The role of corporate ethics management system in ethical decision making: an empirical study on marketing and sales professionals - Beyhan, Aydın (My University, 2007)
Sirketler ve çalısanları için “İş Ahlakı” kavramı, sürekli degisen ve küresellesen is ortamında sivil toplumun baskısıyla, gün geçtikçe önemini arttırmaktadır. Uzun vadede gelismeyi hedefleyen sirketler kurumsal stratejilerini olusturma asamasında is ahlakı kavramına genel anlamda daha özen göstermek ve ahlaki yönetimi saglayacak yönetsel araçlar ve sisitemler gelistirmek durumundadırlar. Özellikle, kurumların pazarlama ve satıs faaliyetlerinin toplum tarafından ahlaki açıdan en çok hata yapılan alanlar olarak algılanması, bu alanda çalısanların karar ve davranıslarına büyük önem vermelerini gerektirmektedir. Bu geri plan ısıgında, bu çalısmada öncellikle “Pazarlama Ahlakı” genelinde ve “Ahlaki Karar Verme” özelinde kapsamlı bir literatür özeti olusturulmustur. Söz konusu literütürden yararlanılarak bir “Kurumsal Ahlak Yönetim Sistemi” (Kurumsal Ahlak Yönetim Sistemi – KAYS) önerilmis ve söz konusu sistemin pazarlama ve satıs professyonellerinin “Kisisel Satısta Ahlaki Duyarlılık” larına etkisi incelenmistir. “Kisisel Satısta Duyarlılıgı” ölçmek üzere bir ölçek (Kisisel Satısta Duyarlılık) gelistirilmistir. Arastırmamız, “Kurumsal Ahlaki Yönetim Sisteminin” pazarlama ve satıs professonellerin “Kisisel Satısta Ahlaki Duyarlılıklarındaki” degisikligi ufak bir oranda açıklayabildigini ortaya koymustur. Ancak, diger bir taraftan, pazarlama ve satıs profesyonellerinin farklı departmanlarlala yaptıkları toplantıların sıklıgı ve “Ahalakın” kurumun resmi ceza/ ödül sistemine entegre edilmesi “Ahalaki Duyarlılık” acısından önemli bulunmustur. Daha geçerli genellemelere ulasmak için bu çalısmaya konu olan üç sektörün dısındaki profesyonnellerle yeni arastırmaların yapılması dogru olacaktır.

In an the ever-changing and globalizing business environment, due to the increased public pressure, the concept of “Business Ethics” is gaining more and more importance both for the individuals and corporations alike. The firms, who aim to achieve long-term growth need to develop and utilize “Corporate Ethics Management Systems”. Since the public considers that marketing and sales functions of the businesses are where the most of the unethical behavior takes place, professionals in these areas need to pay more attention to their decisions and actions. With this background in mind, in this work a broad literature review in “Marketing Ethics”, with a focus on “Ethical Decision Making”, has been compiled. Later, based on the currently available literature a “Corporate Ethics Management System” (Corporate Ethics Management System – CEMS) has been developed and the affect of the system on “Ethical Awareness in Personal Selling” of marketing and sales professionals has been investigated. In order to measure “Ethical Awareness” in sales a scale (Ethical Awareness in Personal Selling) has been developed. This research suggests that “Corporate Ethics Management Systems”, such as the one offered in this study (CEMS), can only account for minor variations in the “Ethical Awareness in Personal Selling” of the sales and marketing professionals. However, frequency of interdepartmental meetings involving marketing and sales professionals and the integration of ethics into the official reward and punishment systems were found to be significant in the “Ethical Awareness in Personal Selling” of the marketing and sales professionals. In order to reach precise generalization, further research should be conducted with professionals from different sectors beyond the three sectors investigated here.
Keywords: Etik_İş; İş Ahlakı_İşletmeler; Karar Verme (Ahlak)_İşletmeler; Kurumsal Ahlaki Yönetim Sistemi